Operating Room Clinicians' Attitudes and Perceptions of a Pediatric Surgical Safety Checklist at 1 Institution. Issue 1 (March 2016) - Norton, Elizabeth K.; Singer, Sara J.; Sparks, William; Ozonoff, Al; Baxter, Jessica; Rangel, Shawn
Abstract : Background: Despite mounting evidence that use of surgical checklists improves patient morbidity and mortality, compliance among surgical teams in executing required elements of checklists has been low. Recognizing that clinicians' receptivity is a major determinant of checklist use, we conducted a survey to investigate how mandated use of a surgical checklist impacts its operating room clinicians' attitudes about and perceptions of operating room safety, efficiency, teamwork, and prevention of medical errors. Methods: Operating room clinicians at 1 pediatric hospital were surveyed on their attitudes and perception of the novel Pediatric Surgical Safety Checklist and the impact the checklist had on efficiency, teamwork, and prevention of medical errors 1 year after its implementation. The survey responses were compared and classified by multidisciplinary perioperative clinical staff. Results: Most responses reflected positive attitudes toward checklist use. The respondents felt that the checklist reduced complications and errors and improved patient safety, communication among team members, teamwork in complex procedures, and efficiency in the operating room. Many operating room staff also reported that checklist use had prevented or averted an error or a complication. Perceptions varied according to perioperative clinical discipline, reflecting differences in perspectives. For example, the nurses perceived a higher rate of consent-related errors and site marking errors than did the physicians; the surgeons reported more antibiotic timing and equipment errors than did others. Conclusions: The surgical staff at 1 pediatric hospital who responded viewed the novel Pediatric Surgical Safety Checklist as potentially beneficial to operative patient safety by improving teamwork and communication, reducing errors, and improving efficiency. Responses varied by discipline, indicating that team members view the checklist from different perspectives.